2013
DOI: 10.1186/1476-9255-10-37
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AIM2 is high and correlated with inflammation in hepatitis B virus associated glomerulonephritis

Abstract: Background & aimsInnate immunity is the first line of defense against invasive microbial infection, and AIM2 plays an important role in this process by sensing double-stranded DNA viruses. However, the role of AIM2 in regulating the immune response to viruses in vivo, especially in sensing hepatitis B virus (HBV), has not been examined. We hypothesized that the expression of AIM2 increases corresponding to HBV-mediated inflammation in patients with hepatitis B virus associated glomerulonephritis (HBV-GN), a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The same study also showed that patients with higher levels of serum HBV-DNA had lower level of serum complement, suggesting a correlation between serum HBV-DNA levels and the deposition of immune complexes, and the existence of a mechanism involving HBV-related immune complexes formed by passive trapping or in situ formation. Du et al[ 35 ] demonstrated that high levels of serum HBV-DNA correlated with the expression of inflammatory factors in renal biopsy specimens from HBV-GN patients. Deposition of immune complexes in the kidney is perceived to play a pivotal role in the pathogenesis of HBV-related nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also showed that patients with higher levels of serum HBV-DNA had lower level of serum complement, suggesting a correlation between serum HBV-DNA levels and the deposition of immune complexes, and the existence of a mechanism involving HBV-related immune complexes formed by passive trapping or in situ formation. Du et al[ 35 ] demonstrated that high levels of serum HBV-DNA correlated with the expression of inflammatory factors in renal biopsy specimens from HBV-GN patients. Deposition of immune complexes in the kidney is perceived to play a pivotal role in the pathogenesis of HBV-related nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of AIM2, IL-1β and IL-18 in hepatitis B virus (HBV) infected human PBMCs correlates with viral load, and AIM2 expression is lower in chronic as compared to acute cases [26]. AIM2 expression also correlates with renal damage during HBV infection, possibly indicating that AIM2 enhances immunopathology during HBV infection [27,28], but a definitive role remains to be determined.…”
Section: Alr Inflammasomesmentioning
confidence: 99%
“…The expression levels of absent in melanoma 2 (AIM2), during HBV infection or replication, have been found to be elevated. This generates inflammatory state and contributes to renal damage [135]. Also, TLR3-signalling has been implicated in HCV-related glomerular disease [136].…”
Section: Inflammation and Extra Hepatic Manifestations As A Results Ofmentioning
confidence: 99%